Investigating acquired temozolomide resistance in adult glioblastoma - Wong, ZY (2020)
Glioblastoma is the most aggressive primary malignant brain tumour in adults with very poor prognosis. Current management includes surgery, radiotherapy and temozolomide (TMZ), which causes three types of DNA methylation: O6-methylguanine (O6-meG), N7-methylguanine and N3-methyladenine. N-methylated lesions are mostly recognised and repaired by base excision repair (BER), while the most toxic DNA adduct is O6-meG. This is directly repaired by O6-methylguanine-DNA methyltransferase (MGMT), and subsequently degraded. If not removed, O6-meG leads to mispairing, futile cycles of mismatch repair (MMR) and eventually double strand breaks. The acquisition of TMZ resistance presents a major clinical challenge; mechanisms reported to be involved include MGMT upregulation, MMR deficiency and drug efflux. We hypothesise that more genes contributing to acquired TMZ resistance are yet to be identified. To better understand this resistance, TMZ-resistant sublines T-20 and T-100 were generated from TMZ-sensitive, MGMT-negative GaMG parental cells by previous students, by exposure to TMZ concentrations equivalent to cerebrospinal fluid and plasma levels. Herein, the TMZ-resistant phenotype was confirmed, and T-20 and T-100 cells were found to be cross-resistant to other methylating agents MNU and MMS but not intercalating agent MMC. MGMT was markedly overexpressed in TMZ-resistant cells and was reduced after TMZ exposure, suggesting that TMZ was entering the cells and causing MGMT consumption, hence making an efflux pump resistance mechanism unlikely. TMZ resistance was partially reversed in T-20 but not at all in T-100 by MGMT inhibitor O6-benzylguanine. Neither was there change in expression of MMR proteins, suggesting MGMT/MMR-independent resistance. To investigate potentially novel resistance mechanisms, scRNA-seq data generated by a previous student were examined. These revealed significant transcriptional differences, with upregulation of genes including MGMT, BCAT1, CT83, CPNE8 in resistant sublines and EBF1, E2F1, RRM2 in GaMG parental cells, which were then validated using RT-qPCR. There were no significant changes in viability after siRNA depletion of EBF1 and E2F1 in GaMG cells, or CPNE8, BCAT1 and CT83 both alone or together in T-20 and T-100 cells. The effect of co-targeting multiple genes was tested, based on the hypothesis that TMZ resistance has multiple drivers. MGMT inhibition alongside BCAT1:CT83 co-depletion might have partially reversed TMZ resistance but results were inconsistent. Nevertheless, cell viability in the absence of TMZ was reduced upon BCAT1:CT83 co-depletion and the percentage change in T20 and T100 was greater than in parental cells. This suggested that even if BCAT1 and CT83 were not individually driving TMZ resistance, the cells might be more dependent on these genes for viability. Further investigation of the differentially expressed proteins and their signalling pathways could complement the scRNA-seq data to improve accuracy of identifying potential novel mediators, which may help to suggest new approaches to GBM therapy.